Codex, Roll, and Libraries in Oxyrhynchus - Barker, Don C. (Tyndale bulletin, 2006)
The fragmented discards of a library from the ancient city of Oxyrhynchus in middle Egypt provide us with an excellent ‘sample’ to conduct a comparative analysis with the contemporary Christian books from the same city. Both the secular and the Christian books in general share common features except for their construction: the library books are rolls whereas the Christian books are in the codex format. What led the Christians to choose this ‘new technology’? Could it be that the driving reason was the protection of the contents against tampering?